Avoiding Ethanol Presence in DNA Samples Enhances the Performance of Ultraviolet Resonance Raman Spectroscopy Analysis. - Cammisuli, Francesca; Pascolo, Lorella; Morgutti, Marcello; Gessini, Alessandro; Masciovecchio, Claudio; D'Amico, Francesco (Appl Spectrosc, 2017)
Ethanol is an essential chemical reagent in DNA preparation as its use increases the yield of extraction. All methodologies for DNA isolation involve the use of ethanol in order to prevent DNA dissolution in water and to optimize the binding of DNA to chromatographic membranes. In this note, we show how the presence of ethanol traces in DNA aqueous solution affects ultraviolet Raman spectra, leading to possible misinterpretations. We report a simple method to remove the ethanol Raman features from the spectra, based on heating the DNA sample at 80 ℃, followed by a slow cooling procedure.
Keywords: DNA; Ethanol; Female; Humans; Placenta; Pregnancy; Spectrophotometry, Ultraviolet; Spectrum Analysis, Raman